ISSUES OF RELIGIOUS MINORITIES IN PAKISTAN (2008-2022) - Rida Saleem; Bano Qudsia; Aleezah Saeed; Mujahid Hussain Millu (International Journal of Contemporary Issues in Social Sciences, 2023)
Pakistan, as a Muslim-majority country, hosts significant religious minority populations comprising Hindus, Sikhs, Ahmadiyyas, Christians, and others. Despite legislative measures aimed at protecting these minorities, they continue to face marginalization and discrimination across multiple dimensions, including social, political, economic, legislative, and psychological issues. Therefore, this research paper examines the issues of religious minorities in Pakistan from 2008 to 2022. The data of this research is collected from secondary sources which include newspapers, Journals, e-books etc. It analyzes the issues of religious minorities in Pakistan as a human rights issue of significant concern. It explores the factors contributing to the marginalization. The implications of mistreating religious minorities are analyzed both nationally and internationally. To address the issues faced by religious minorities in Pakistan, a multi-faceted approach is recommended.